The influence of dipeptidyl peptidase-4 inhibitor on the progression of type B intramural hematoma - Chen, Qu; Jiang, Dandan; Shan, Zhonggui (Frontiers in Cardiovascular Medicine, 2022)
Abstract Objectives Investigating whether dipeptidyl peptidase-4 inhibitors (DPP4i) could influence the progression of type B intramural hematoma (IMHB) in patients with diabetes mellitus (DM). Methods Uncomplicated IMHB patients were matched by age, sex, and body mass index. Cox proportional hazard models were constructed to identify risk factors. A Kaplan–Meier survival analysis was used to estimate all-cause and aorta-related mortality. Results Ninety-six matched IMHB patients were divided into Group A (n=32, IMHB patients without DM), Group B (n=32, IMHB patients with DM receiving oral antidiabetic drugs [without DPP4i]) and Group C (n=32, IMHB patients with DM receiving oral antidiabetic drugs [with DPP4i]). Group C had the lowest rate of aorta-related adverse events (3.1%), aorta-related mortality (0.0%) and reintervention (3.1%). Cox proportional hazard models revealed that a lower eosinophil count (per 0.1, HR, 0.48; 95% CI, 0.29-0.79, P=0.004) and a higher neutrophil to lymphocyte ratio (NLR) (HR, 1.13; 95% CI, 1.05-1.21, P=0.001) were associated with higher occurrences of aorta-related adverse events. A lower eosinophil count (per 0.1, HR, 0.40; 95% CI, 0.18-0.89, P=0.025) and a higher NLR (HR, 1.19; 95% CI, 1.08-1.32, P=0.001) were also associated with increased aorta-related mortality. Conclusions DPP4i administration in DM patients with IMHB was associated with lower aorta-related mortality and more benign progression than in those who did not receive DPP4i or those without DM. Furthermore, a higher eosinophil count and a lower NLR ratio are potential protective factors that may explain the potential therapeutic benefit of DPP4i.